PEMBELAJARAN KOOPERATIF STAD DAPAT MENINGKATKAN HASIL BELAJAR SISWA SMTK DIASPORA KABUPATEN SORONG - Habel S.J. Rieuwpassa (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is a Classroom Action Research (PTK) with research subjects being class XI students of Diaspora Vocational High School, Sorong Regency who have not yet achieved the KKM in the WWTP subject as many as 18 students from 23 students. The results of the pre-cycle carried out through teaching were carried out for class XI students on April 27 2018, it was known that of the 23 students, 5 students had completed the KKM and 5 students had not yet reached the KKM. Minimum Completeness Criteria (KKM) for Biblical Studies. The purpose of this research is to improve the results of studying the Biblical Science Subject for class XI at the Diaspora Vocational High School, Sorong Regency. The research stages are (1) planning, (2) action, (3) reflection. The research was conducted in 2 cycles and each cycle consisted of 1 action. The indicator of research success refers to the KKM Biblical Science class XI of Diaspora Vocational High School, Sorong Regency, the research is said to be successful if all students have reached KKM 70. The results of PTK show that after implementing the action using the STAD type Cooperative learning model in the subject of Biblical Science material on the Book of the Prophets Prophet students experienced a significant increase. This can be seen from the scores obtained by students in cycle I and cycle II when compared to the initial conditions 18 students did not complete, then in cycle I it was found that 11 students did not complete and cycle II found only 2 students did not complete, so the results of completeness after learning with STAD model mastery of students in learning as many as 21 students from 23 students. The conclusion is that the application of the STAD Type Learning Model can improve learning outcomes in class XI students of SMTK Diaspora, Sorong Regency. Keywords: Learning Outcomes, Cooperative Learning, STAD, SMTK DIASPORA